2024
DOI: 10.1063/5.0195085
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent flow influences plant root growth: A phytofluidics approach

Prasenjeet Padhi,
Sumit Kumar Mehta,
Kaushal Agarwal
et al.

Abstract: The challenges of food security are exacerbated by the world's expanding population and diminishing agricultural land. In response, hydroponic cultivation offers a potentially more sustainable approach to growing nutrient-dense crops compared to traditional methods. Motivated by this understanding, we conducted a series of experiments to explore the behavior of Brassica juncea (Pusa Jaikisan) plant roots under various flow configurations within a controlled environment. The flow configurations considered were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…The device was fabricated using a vinyl-terminated polydimethylsiloxane (SYLGARD™ 184 Silicone Elastomer, Sigma Aldrich®, USA) substrate, following an inexpensive wire-drawing method with adaptations from published methods. 51–53 It was then soft-baked at 45 °C for 10 hours in a hot air oven (IKON™ Instruments, India). Kindly refer to the ESI† for the 3D-printed ABS mold and casting setup of the wire-drawing method.…”
Section: Methodsmentioning
confidence: 99%
“…The device was fabricated using a vinyl-terminated polydimethylsiloxane (SYLGARD™ 184 Silicone Elastomer, Sigma Aldrich®, USA) substrate, following an inexpensive wire-drawing method with adaptations from published methods. 51–53 It was then soft-baked at 45 °C for 10 hours in a hot air oven (IKON™ Instruments, India). Kindly refer to the ESI† for the 3D-printed ABS mold and casting setup of the wire-drawing method.…”
Section: Methodsmentioning
confidence: 99%
“…In various research endeavors, the fluid medium utilized in electroosmosis is commonly identified as a Newtonian fluid. , Conversely, within biological contexts, non-Newtonian fluids found in living organisms are termed biofluids, encompassing colloidal suspensions, polymer solutions, and interstitial fluids such as blood, saliva, proteins, and DNA solutions. Despite the nonlinear rheological characteristics exhibited by non-Newtonian fluids, including variable viscosity and alterations in normal stress, Newtonian fluids are typically assumed to possess a consistent viscosity. Delving into EOF phenomena of non-Newtonian fluids holds significance for optimizing the performance of diverse micro/nanofluidic devices and refining experimental setups. …”
Section: Introductionmentioning
confidence: 99%